2012
DOI: 10.1097/mao.0b013e3182659d02
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Late Potentials in Normal-Hearing Adult Subjects With Down’s Syndrome

Abstract: Our study demonstrated that ALP longer latencies are present in adult DS participants even when they have a normal hearing threshold, regardless of handedness and head size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…Such findings corroborate those of previous studies in which no statistically significant differences were found between the ears for latency values of the BAEP and P300 in audiologically normal individuals and in individuals with Down syndrome (21,22) . These results reinforce the fact that, for individuals with DS, the reference values and analysis criteria for the BAEP and P300 with non-complex stimuli (clicks and tone burst) can be used equally for both ears, as it already occurs in clinical practice in individuals with typical development.…”
Section: Discussionsupporting
confidence: 83%
“…Such findings corroborate those of previous studies in which no statistically significant differences were found between the ears for latency values of the BAEP and P300 in audiologically normal individuals and in individuals with Down syndrome (21,22) . These results reinforce the fact that, for individuals with DS, the reference values and analysis criteria for the BAEP and P300 with non-complex stimuli (clicks and tone burst) can be used equally for both ears, as it already occurs in clinical practice in individuals with typical development.…”
Section: Discussionsupporting
confidence: 83%
“…1979 ), reduced electrical permeability of neural membranes and dendritic spine numbers ( Lott and Dierssen 2010 ), as well as changes in synaptic morphology ( Scott et al. 1983 ; Lott and Dierssen 2010 ) could underlie the reduced cerebral reactivity in people with DS ( Arisi et al. 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have highlighted differences between the DS and TD populations in the form of longer movement onset and reaction times (Arisi, et al, 2012;Davis, Sparrow, & Ward, 1991;Henderson, Illingworth, & Allen, 1991;Masumoto, Abe, & Inui, 2012), longer movement times, and greater movement errors for DS compared to TD (Elliott, Welsh, Lyons, Hansen, & Wu, 2006;Hodges, Cunningham, Lyons, Kerr, & Elliot, 1995). These perceptual-motor impairments have been attributed to both central processes (i.e., Frith & Frith, 1974) and peripheral anatomical characteristics (Henderson et al, 1991;Morris, Vaughan, & Vaccaro, 1982).…”
Section: Introductionmentioning
confidence: 99%